2009
DOI: 10.1177/0002764209347630
|View full text |Cite
|
Sign up to set email alerts
|

From Public Diplomacy to Corporate Diplomacy: Increasing Corporation’s Legitimacy and Influence

Abstract: Public diplomacy is an increasing popular preoccupation of governments worldwide, especially aimed at achieving acceptance of their foreign policies abroad, in which corporations have traditionally played a secondary role. However, as it happens with governments, corporations have understood long ago the challenges of being accepted abroad. In this paper the authors suggest that 'corporate diplomacy' is also a process by which corporations intend to be recognized as representatives of something that might be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 12 publications
1
71
0
7
Order By: Relevance
“…Previous studies have related CD to PCSR (Westermann-Behaylo et al, 2015;White et al, 2011) and suggested embedding CD in a PCSR framework, since PCSR recognizes "the power of corporations in society and the responsible use of power in the political arena" (White et al, 2011, p. 283). In fact, social power and political responsibilities are key aspects of CD (Mogensen, 2017;Ordeix-Rigo & Duarte, 2009). Moreover, the core challenges of CD lie in responding to social pressure through external stakeholders and meeting the expectations of (foreign) corporate stakeholders in order to gain legitimacy (Ordeix-Rigo & Duarte, 2009;Weber & Larsson-Olaison, 2017).…”
Section: Political Csr Research In Corporate Diplomacymentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have related CD to PCSR (Westermann-Behaylo et al, 2015;White et al, 2011) and suggested embedding CD in a PCSR framework, since PCSR recognizes "the power of corporations in society and the responsible use of power in the political arena" (White et al, 2011, p. 283). In fact, social power and political responsibilities are key aspects of CD (Mogensen, 2017;Ordeix-Rigo & Duarte, 2009). Moreover, the core challenges of CD lie in responding to social pressure through external stakeholders and meeting the expectations of (foreign) corporate stakeholders in order to gain legitimacy (Ordeix-Rigo & Duarte, 2009;Weber & Larsson-Olaison, 2017).…”
Section: Political Csr Research In Corporate Diplomacymentioning
confidence: 99%
“…2 2015; Mogensen, 2017;Ordeix-Rigo & Duarte, 2009). By engaging in CD, multinational companies are able to respond to changing social expectations and to grow their legitimacy and influence in their host countries (Ordeix-Rigo & Duarte, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…C) La legitimidad y el medio plazo La industria automovilística, las eléctricas, el sector tecnológico y logístico, así como la administración pública de ambos países están esperando que los grupos influentes de la sociedad se activen y actúen como verdaderos actores de cambio social. El conocido social engagement es de vital importancia en el proceso comunicativo institucional (Ordeix, Duarte, 2009). La influencia de base o soporte social es de suma relevancia, como para vencer los agravios comparativos con el uso del coche convencional, y poder potenciar su producción en serie.…”
unclassified
“…9 Regularly, non-traditional foreign policy players are not recognized formally as actors under international law, that is their access to institutionalized fora such as UN bodies is restricted. De facto, however, they are present, at times gaining observer or more wide-reaching formal statuses, and are informally fully involved in a broad array of global politics, ranging from financial, through development, to environmental governance (Betsill and Corell, 2008;Ordeix-Rigo and Durante, 2009;Fogarty, 2012). This implies that they acquire such notoriety that other foreign policy actors cannot afford to ignore their demands, and that a real competition between various (types of) players inevitably sets in.…”
Section: Global Governance Induces Competition Among Multiple Types Omentioning
confidence: 99%